ROLES OF ARTIFICIAL INTELLIGENCE IN EDUCATION FOR SUSTAINABLE DEVELOPMENT IN ASIA-PACIFIC CONTEXTS - Hara, Masatoshi (Global journal of Business and Integral Security, 2024)
This study explores the intersection of artificial intelligence (AI) and sustainable educational development in Asian contexts, proposing a framework to delineate the multifaceted roles of AI in fostering educational advancement. By embracing AI innovations while upholding principles of equity, inclusivity, and ethical governance, Asian nations can forge a more resilient and equitable educational landscape. The suggested framework encompasses inputs, outputs, and AI converters, prioritizing educational access and completion, particularly in low- and lower-middle-income countries, and emphasizing higher education expansion and research in higher-income nations. Outputs include enhanced employability, job creation, and productivity, whereas concerns revolve around overreliance on technology, bias, digital divide, and job displacement. Policy implications highlight the need for awareness campaigns, policy reforms, infrastructure investment, and partnerships to maximize AI benefits while mitigating potential challenges. However, the study’s conceptual framework lacks a specific methodology, warranting the development of robust research methods tailored to investigate AI’s roles in promoting education for sustainable development. This initial study serves as a foundation for future research endeavors in this burgeoning field.